Floor Composition Affects Performance and Muscle Fatigue Following a Basketball Task - Streepey, J. W.; Gross, M. M.; Martin, B. J.; Sundravalli, S. (Journal of Applied Biomechanics, 2000)
The relationship between playing surface and muscle fatigue was examined in 22 male subjects performing a simulated basketball task on a conventional wood floor and less stiff composite floor. Force and electromyographic activity (EMG) were measured during maximum and submaximum (10% of maximum) voluntary contractions of knee extensor and ankle plantarflexor muscles before and after completion of the simulated basketball task. Jump height was evaluated during the task, and perceived fatigue was assessed at the end of the task. Although not all subjects jumped significantly higher on the composite floor compared to the wood floor, competitive basketball players showed a significant improvement in jump height (3.4 cm, 6%) when jumping on the composite floor. Perceived fatigue was significantly lower for the composite floor (21.7%) than the wood floor (30.2%). The objective measures indicated the occurrence of fatigue; however, force and EMG magnitudes obtained during maximum exertions were not sensitive to floor types. Post-task increase in EMG magnitude indicated a significant fatigue effect for the soleus muscle on the wood floor only. These findings suggest that the composite floor may benefit human performance without increasing fatigue during basketball-related activities.